2008
DOI: 10.1101/sqb.2008.73.009
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Stem Cell Differentiation by Histone Methyltransferases and Demethylases

Abstract: The generation of different cell types from stem cells containing identical genetic information and their organization into tissues and organs during development is a highly complex process that requires defined transcriptional programs. Maintenance of such programs is epigenetically regulated and the factors involved in these processes are often essential for development. The activities required for cell-fate decisions are frequently deregulated in human tumors, and the elucidation of the molecular mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 98 publications
(147 reference statements)
0
23
0
1
Order By: Relevance
“…We showed that the expression of ChM-I was down-regulated by histone modifications in stem cells and some types of differentiated cells. The epigenetic status is induced and maintained by a number of intrinsic histone modifiers (30). In this study, we found that YY1 and p300 are main modifiers of histone associated with the core-promoter region of the ChM-I gene.…”
Section: Discussionmentioning
confidence: 65%
“…We showed that the expression of ChM-I was down-regulated by histone modifications in stem cells and some types of differentiated cells. The epigenetic status is induced and maintained by a number of intrinsic histone modifiers (30). In this study, we found that YY1 and p300 are main modifiers of histone associated with the core-promoter region of the ChM-I gene.…”
Section: Discussionmentioning
confidence: 65%
“…Epigenetic modifications of the chromatin structures, including histone deacetylations, play an essential role in regulating the pluripotency of stem cells and progenitor reprogramming [24,25,26,27,45,46,47]. Hdacs link chromatin structure and transcription factors, and exert epigenetic control of transcriptional activity by removing negatively charged acetyl groups from lysine residues in histones, leading to chromatin condensation and limiting the accessibility of transcription factors to the DNA.…”
Section: Resultsmentioning
confidence: 99%
“…The three polycomb group proteins of the PRC2 complex are all required for EZH2 histone methyltransferase activity, and loss of either Suz12 or Eed results in a global loss of H3K27me2 and -me3 (29,30). Importantly, the activity of the PRC2 complex is required for development, stem cell differentiation, and epigenetic inheritance (8,(31)(32)(33)(34). For example, loss of Suz12 causes embryonic death during early postimplantation stages, and the Suz12-deficient embryos contain diminished levels of H3K27me2 and H3K27me3 in vivo (34).…”
mentioning
confidence: 99%